HUBUNGAN KECANDUAN BERMAIN GAME ONLINE PADA SMARTPHONE DENGAN KUALITAS TIDUR SISWA SMAN 1 KERUAK TAHUN 2020 - Panji Wage Kosasih; Danang Nur Adiwibawa; Irwan Syuhada; Yolly Dahlia (Nusantara Hasana Berdikari, 2022)
World Health Organization (WHO) in 2018 classifies addiction playing online game into the International Classification of Disease11th/ ICD-11). Addicted to playing online games is defined as a pattern ofbehavior gaming or playing (